Kartagener Syndrome: A Rare Cause of Infertility - Kadir Bakay; Davut Güven; İdris Koçak (Medical Network, 2016)
Kartagener's syndrome is defined as motility dysfunction of the epithelial cilia lining the respiratory tract, fallopian tubes and the flagella of the sperm and genetically classified as a rare autosomal recessive disease consisting almost half of all primary ciliary dyskinesia cases. In this brief case review we aim to share our experience concerning Kartagener's syndrome from a gynecologic point of view regarding an unexplained infertility patient.